Tribological properties, corrosion resistance and biocompatibility of magnetron sputtered titanium-amorphous carbon coatings - Dhandapani, Vishnu Shankar; Ramesh, Subbiah; Thangavel, Elangovan; Arumugam, Madhankumar; Park, Kwideok; Gasem, Zuhair M.; Veeraragavan, Veeravazhuthi; Kim, Dae-Eun (ELSEVIER SCIENCE BV, 2016)
Amorphous carbon incorporated with titanium (a-C:Ti) was coated on 316L stainless steel (SS) by magnetron sputtering technique to attain superior tribological properties, corrosion resistance and biocompatibility. The morphology, topography and functional groups of the nanostructured a-C:Ti coatings in various concentrations were analyzed using atomic force microscopy (AFM), Raman, X-Ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). Raman and XPS analyses confirmed the increase in sp(2) bonds with increasing titanium content in the a-C matrix. TEM analysis confirmed the composite nature of the coating and the presence of nanostructured TiC for Ti content of 2.33 at.%. This coating showed superior tribological properties compared to the other a-C:Ti coatings. Furthermore, electrochemical corrosion studies were performed against stimulated body fluid medium in which all the a-C:Ti coatings showed improved corrosion resistance than the pure a-C coating. Preosteoblasts proliferation and viability on the specimens were tested and the results showed that a-C:Ti coatings with relatively high Ti (3.77 at.%) content had better biocompatibility. Based on the results of this work, highly durable coatings with good biocompatibility could be achieved by incorporation of optimum amount of Ti in a-C coatings deposited on SS by magnetron sputtering technique. (C) 2016 Elsevier B.V. All rights reserved.